ISIENSI KREATIVITAS DESA PEKRAMAN DALAM PEMBANGUNAN DESA WISATA DI DESA SANGEH KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Luh Kompyang Sari (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Bali is a Tourist Destination Region that has tourist attraction spread in every Regency. Badung Regency has several villages that made as a tourist destination. One of the tourist villages is Sangeh Village. To be able to make the existing village into a tourist village, certainly not easy, needed a process, strategy to explore the existing potential of both culture, nature and environment by empowering the community of the village. “Indigeneus Knowledge” (lokal knowledge and skills) possessed by the lokal community is very potential to be developed as a component of tourism. In the face of increasingly complex competition and global economic competition, creativity becomes crucial to create competitive advantage, and business continuity. The sustainability of the Tourism Village requires a creative and innovative human, entrepreneurial spirit. Form of activity, creativity of the community in supporting development of Sangeh Tourism Village. The concept is able to empower the community to be able to provide quality services to tourists with a commitment to lokal wisdom. Structuring the environment to be able to provide a peaceful, relaxed, familial atmosphere, away from the modern lifestyle that is full of pressure, comfortable, able to create togetherness between tourism actors, travel service providers and other related and able to lift, display lokal and traditional products.Keyword : Creative, Local Community, Tourism, Village.